2012
DOI: 10.2174/1874357901206010012
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Measles Vaccine Virus as a Vector to Deliver Respiratory Syncytial Virus Fusion Protein or Epstein-Barr Virus Glycoprotein gp350

Abstract: Live attenuated recombinant measles vaccine virus (MV) Edmonston-Zagreb (EZ) strain was evaluated as a viral vector to express the ectodomains of fusion protein of respiratory syncytial virus (RSV F) or glycoprotein 350 of Epstein-Barr virus (EBV gp350) as candidate vaccines for prophylaxis of RSV and EBV. The glycoprotein gene was inserted at the 1st or the 3rd position of the measles virus genome and the recombinant viruses were generated. Insertion of the foreign gene at the 3rd position had a minimal impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 66 publications
0
31
0
Order By: Relevance
“…Therefore, the recombinant gp350 1-443 induced stronger lymphoproliferative responses than RVVgp150. Recombinant gp350 expressed in CHO cells (Cui et al 2013) and measles virus (Mok et al 2012) have been shown to induce significantly high-level production of IL-4 and IFN-γ. The splenocytes from gp350 1-443 -immunized mice also displayed increased production of IFN-γ, TNF-α, IL-4, and IL-10.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the recombinant gp350 1-443 induced stronger lymphoproliferative responses than RVVgp150. Recombinant gp350 expressed in CHO cells (Cui et al 2013) and measles virus (Mok et al 2012) have been shown to induce significantly high-level production of IL-4 and IFN-γ. The splenocytes from gp350 1-443 -immunized mice also displayed increased production of IFN-γ, TNF-α, IL-4, and IL-10.…”
Section: Discussionmentioning
confidence: 99%
“…The second more recent study (Mok et al, 2012) also demonstrated protection from RSV challenge using rMVs expressing RSV-F in the cotton rat model. The RSV-F molecule that was cloned was C-terminally truncated (i.e.…”
Section: Groupsmentioning
confidence: 94%
“…Recombinant measles vectors may be considered for the construction of paediatric vaccines for other paramyxoviruses such as mumps virus (Wang et al, 2001) or respiratory syncytial virus (RSV) (Mok et al, 2012;Sawada et al, 2011;Yamaji & Nakayama, 2014). The attenuated mumps virus is already included in the paediatric cocktail vaccine together with measles and rubella viruses (MMR).…”
Section: Introductionmentioning
confidence: 99%
“…Following RSV/A2 challenge, the vaccinated cotton rats were protected from pulmonary replication. This vaccine was also evaluated in rhesus macaques, where it showed similar efficacy inducing a strong RSV F-specific antibody response [153].…”
Section: Vector-basedmentioning
confidence: 99%